Spontaneous hemoperitoneum in pregnancy: a rare case report - Singh, Anuradha; Aggarwal, Kiran; Krishna, Nikita; Sinha, Shivangini; Lal, Prabha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Spontaneous hemoperitoneum in pregnancy (SHiP) is a rare but life-threatening condition with an estimated incidence rate of 0.04 per 1000 births. It is characterized by the accumulation of blood in the peritoneal cavity without trauma or obvious cause in pregnancy and up to 42 days postpartum that lead to significant maternal and perinatal complications. SHiP mostly occurs in third trimester of pregnancy with an incidence of 27% in the second trimester. A 40-year-old multigravida female at 30 weeks of gestation who presented with acute abdominal pain. Urgent imaging revealed a small amount of free fluid in perihepatic and perisplenic space with blood clots highly suggestive of hemoperitoneum. An emergency laparotomy was performed which confirmed the diagnosis and approximately 1-1.5 litres of hemoperitoneum with 1 litre of blood clot from pouch of douglas were evacuated. Caesarean section was performed at the same time placenta was delivered with intact membranes. There was atonic post-partum haemorrhage (PPH) which was not medically managed, so in view of doubt of rent in lower uterine segment with increased vascularity over the post surface, atonic PPH and general condition of the patient, total abdominal hysterectomy was done. Total blood loss was 3.5 litres. Both mother and baby recovered without further complications. This case highlights the importance of early recognition and prompt surgical intervention in SHiP to prevent maternal and fetal morbidity and mortality. Given its rarity and non-specific presentation, SHiP remains a diagnostic challenge and requires a high index of suspicion in pregnant women with acute abdomen and hemodynamic instability.